PHYSIOTHERAPEUTIC TECHNIQUES FOR EXAMINATION, DIAGNOSIS AND TREATMENT IN EHLERS-DANLOS SYNDROME AND THE QUALITY OF ITS EVIDENCE: SYSTEMATIC REVIEW 2010-2020. - Acuña Ferreto, Elías (2024)
Ehlers-Danlos syndrome (EDS) can be understood as a heterogeneous group of hereditary disorders of the connective tissue, with an abnormal synthesis of collagen, associated with a genetic mutation, leading to alterations in tissues such as skin, ligaments, joints, blood vessels. and other organs. Among the limitations for the physiotherapeutic approach to EDS, the scientific literature to date is small and limited, and the exact clinical management that can be provided is unknown. The objective for this research was to identify the physiotherapeutic examination, diagnosis and treatment techniques in EDS and the quality of the evidence, through a systematic review 2010-2020. Thirty-three scientific articles were reviewed in which methods and techniques for examination, diagnosis and treatment were identified, evidencing clinical reasoning for each phase of the approach. In addition, it was found that 15.2% of the articles presented quality of 1++, 6.0% with quality of 1+, another 6.0% with quality of 1-, 12.1% with quality 2++, 21.2% with quality 2+, 3.0% with quality 2-, 27.3% with quality 3 and 9.1% with quality 4 under the criteria of the Scottish Intercollegiate Guidelines Network. In conclusion, regarding the level of evidence of the selected articles, there is a low and high level, since the majority are between 2++ and 3 according to these criteria.